REVIEW: Hong Kong still a sanctuary for dissident media ideas and sparks - Alan Knight (Asia Pacific Network, 2006)
Hugo de Burgh's book does much to illuminate Chinese mainland journalism which he said was inextricably bound up with the often implicit expectations of China's culture. He provided unique insights into their education, practices and philosophies.